Firm Responses to an Interest Barrier: Empirical Evidence - Jarkko Harju; Ilpo Kauppinen; Olli Ropponen (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
Finish VATT Institute for Economic Research economists Jarkko Harju, Ilpo Kauppinen and Olli Ropponen have studied the interesting effects of an interest barrier that was introduced in Finland to restrict the profit-shifting opportunities of multinational enterprises (MNEs). They employed full population data of Finnish, Swedish and Danish MNEs and a difference-indifferences methodology, where Swedish and Danish MNEs serve as a control group. They found that Finnish MNEs responded to the interest barrier by decreasing their financial expenses. Subsidiaries decreased also their long-term debt levels.They did not find evidence of debtshifting being replaced by transfer pricing. Neither did they find evidence of changes in output, suggesting that the interest barrier did not create distortions by affecting the real activity of MNEs.
Keywords: 330